Labour Market Regimes and Patterns of Flexibility: A Sweden-Canada Comparison - Chaykowski, Richard (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "Labor Market Regimes and Patterns of Flexibility: A Sweden-Canada Comparison," by Axel Van Den Berg, Bengt Furaker and Leif Johansson.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; LABOR market; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z